A Call to Standardize Definitions, Data Collection, and Outcome Assessment to Improve Care in Alcohol‐Related Liver Disease. Issue 3 (31st August 2019) - Shen, Nicole T.; Salajegheh, Annaheta; Brown, Robert S.
Abstract : Alcohol‐related liver disease (ALD) is highly prevalent and appears to be increasingly reported with worsening mortality; thus, optimizing care in this patient population is imperative. This will require a multidisciplinary, multifaceted approach that includes recognizing alcohol use disorder (AUD) and existing treatments for AUD. We must also acknowledge the full spectrum of ALD clinically and histologically. For example, our current clinical definitions of alcohol‐related hepatitis (AH) do not address that >95% of severe AH occurs in the setting of cirrhosis with <60% of liver explants having hepatitis. Given that the majority of ALD studies rely on clinical diagnosis and lack pathologic confirmation, prior data on the efficacy of medical treatment or use of transplantation are likely limited by intertrial and intratrial heterogeneity. Added limitations of the current field include the inconsistent reporting of relapse with the use of varying definitions and unreliable assessments. Moreover, studies fail to consistently capture the data variables that likely influence the main outcomes of interest in this population—mortality and relapse—and a global effort to create a standardized data collection tool moving forward could help effectively and efficiently aid in the advancement of this field. Conclusion: To optimize patient care and make best use of a limited resource, a systematic change in the approach to research in this population must be undertaken that creates consistent definitions for use in future research to generate reliable and reproducible results. With this in mind, we concisely reviewed the literature to summarize the current state of treating and managing ALD, the heterogeneity in definitions, and the significant opportunities for clinical and research improvement.